Assessment of autism spectrum disorder - Goldstein, Sam, 1952-; Ozonoff, Sally (New York: The Guildford press, 2018)
"This authoritative resource, now thoroughly revised for DSM-5, has set the standard for the comprehensive assessment of autism spectrum disorder (ASD). Leading experts demonstrate how to craft a scientifically grounded profile of each child's strengths and difficulties, make a formal diagnosis, and use assessment data to guide individualized intervention in clinical and school settings. Chapters review state-of-the-art instruments and approaches for evaluating specific areas of impairment in ASD and co-occurring emotional and behavioral disorders. Considerations in working with children of different ages are highlighted. With a primary focus on children, several chapters also address assessment of adolescents and adults. New to This Edition *Chapter on key implications of DSM-5 diagnostic criteria, plus related updates throughout the volume. *Chapter on advances in early identification (ages 0-3). *Chapter with in-depth case examples illustrating the evaluation decision-making process and common diagnostic challenges. *Chapters on pseudoscience (including strategies for advising parents) and future directions in the field. *Current assessment data, numerous new and revised measures, and cutting-edge screening approaches"--
Revised edition of: Assessment of autism spectrum disorders / edited by Sam Goldstein, Jack A. Naglieri, Sally Ozonoff. 2009.
Includes bibliographical references and index.
Keywords: Autism in children -- Diagnosis; Psychology/ Psychopathology / Autism Spectrum Disorders; Medical / Psychiatry / Child & Adolescent; Social science / Social Work; Education / Special Education / Social Disabilities